Ebû Bekr el-Katîî ve hadis ilmindeki yeri - Gan, Furkan (My University, 2021)
III./ IX. ve IV./ X. yüzyıl, hadis ilminin gidişatını daha iyi anlama açısından önem arzet-mektedir. İlgili dönemlerde Bağdat siyasi ve ilmi açıdan merkezi bir konuma sahipti. Bu-rada Katîatü’d-dakîk mahallesinde yaşayan Ebû Bekr el-Katîî (v. 368/ 979), döneminde “müsnidü’l-Irâk” unvanıyla tanınmıştır. O, muhaddis kimliğinin yanı sıra zâhid bir kişili-ğe sahiptir. Ayrıca Ahmed b. Hanbel’in (v. 241/ 855) Müsned’inin tamamını Abdullah b. Ahmed’den (v. 290/ 903) dinleyen ve rivayet eden tek râvidir. Ancak Katîî’nin Müsned’e yaptığı iddia edilen ziyâdeler/ ilâveler tartışma konusu olmuş, ziyâde yaptığı hususunda ulemâ ittifak etmiş ancak bu ziyâdelerin sayısı hakkında farklı görüşler ileri sürülmüştür. Bunlar arasında İbn Hacer el-Askalânî’nin (v. 852/ 1449) tespitiyle de uyumlu olan Zü-heyr en-Nâsır ve Luheydân’ın dört ziyâde görüşü tercih edilmeye daha uygun görünmek-tedir. Cüz’ü’l-elf dînâr ve el-Fevâid gibi eserleri bulunan Katîî, münekkit muhaddisler nez-dinde güvenilir bir râvi kabul edilmiş, kendisi hakkında müsnidü’l-vakt, sadûk, sika, hâfız sâhibü’s-sünne, müfîd, me’mûn gibi sıfatlar kullanılmıştır. Ta‘dîl niteliği taşıyan bu sıfat-ların yanı sıra Katîî’yi cerh edenler de bulunmaktadır. Nitekim kitaplarını sel baskınında kaybetmesinin ardından semâ yöntemi ile elde etmediği başka nüshalardan kitaplarını yeniden yazması, ömrünün sonlarına doğru ihtilâta uğraması ve görme duyusununun za-yıflaması, mestûr olması ve Müsned’e ziyâdede bulunması gibi durumlar cerh edilmesine neden olmuştur. Neticede onun adalet yönünden sika kabul edildiği; zabt yönünden ise cerhe uğradığı ifade edilebilir.

3rd/ 9th and 4th/ 10th centuries have crucial importance to understand the course of hadīth science in a better way. In the corresponding periods, Baghdād had a pivotal state in terms of political and scholarly spheres. Abū Bakr al-Qatī‘ī (d. 368/ 979), lived in so-called ‘Qatī‘at al-Daqīq’ quartery in there, was known with the title of ‘musnid (ascriber) al-‘Irāq’. He was an ascetic beside being a muhaddith. He is the lone transmitter who lis-tened and transmitted whole of the Musnad of the Ibn Hanbal (d. 241/ 855) from ‘Abd Allāh ibn Ahmad (d. 290/ 903). Yet, the allegedly additions to the Musnad, made by Qatī‘ī are disputed among scholars. The existence of those additions is unanimously accepted, whereas there are divergent consideretions on the number of them. Among these opinions, four additions view of Zuhayr al-Nāṣır and Luḥaydān regarding their number, which is compatible with the evaluation of Ibn Hajar al-Asqalānī (d. 852/ 1449), seems more app-ropriate to accept. Having works namely, Juzz al-Alf Dīnār and al-Fawāid, Qatī‘ī is re-garded as thiqa (trustworthy) transmitter before master hadīth critics and the titles like musnid al-waqt (the isnād owner of the time), sadūq (truthful), thiqa, hāfidh (retentive), sāhib al-Sunnah (the companion of the Sunnah), mufīd (instructor), ma’mūn (honest). Besides these praise titles, there are certain scholars who criticises him. Nonetheless, he was criticised because of re-writing of his books from the manuscripts which are not acquired by the method of samā‘ (audition of hadīth) after when he got lost them in the flood, ikhtilāt (memory lapse/ to became mixed-up) in the late period of his life, decline of his light, being mastūr (outwardly acceptable transmitter) and having additions to the Musnad. Consequently, it can be said that he was regarded as thiqa in terms of ‘adl (truthfulness) and criticised in terms of ḍabt (accuracy).
Keywords: ‘Abd Allāh ibn Ahmad; Abdullah b. Ahmed Ḥadīth; Abū Bakr al-Qatī‘ī; Ahmad ibn Hanbal; Ahmed b. Hanbel; al-Musnad; Baghdād; Bağdat; Ebû Bekr el-Katîî; Hadis; Hadith; Islam; İslam; Musnid al-‘Irāq; Müsned; Müsnidü’l-Irâk; Ziyādāt al- Qatī‘ī; Ziyâdâtü’l-Katîî